Reduction-responsive core-crosslinked hyaluronic acid-b-poly(trimethylene carbonate-co-dithiolane trimethylene carbonate) micelles: synthesis and CD44-mediated potent delivery of docetaxel to triple negative breast tumor in vivo. Issue 19 (25th April 2018) - Zhu, Yaqin; Zhang, Jian; Meng, Fenghua; Cheng, Liang; Feijen, Jan; Zhong, Zhiyuan
Abstract : Docetaxel-loaded core crosslinked HA-P(TMC-DTC) micelles show high targetability to CD44-overexpressing MDA-MB-231 breast tumor and effectively inhibit tumor growth. Abstract : Future cancer therapy relies on the development of simple, selective and bioresponsive nanomedicines. Herein, we report that reduction-responsive core-crosslinked hyaluronic acid- b -poly(trimethylene carbonate- co -dithiolane trimethylene carbonate) micelles (HA-CCMs) can be easily synthesized and achieve efficient CD44-mediated delivery and triggered cytoplasmic release of docetaxel (DTX) to MDA-MB-231 human triple negative breast tumor in vivo . DTX-loaded HA-CCMs exhibited a favorable size of 85 nm, low drug leakage and glutathione-responsive DTX release. HA-CCMs were efficiently taken up by CD44-overexpressing MDA-MB-231 cells as indicated by flow cytometry. DTX-loaded HA-CCMs induced selective apoptotic activity toward MDA-MB-231 cells in vitro . Notably, over 7-fold longer blood circulation time and 4-fold stronger tumor accumulation were observed for DTX-loaded HA-CCMs compared to free DTX. Cy5-labeled HA-CCMs revealed deep tumor penetration at 6 h post injection. DTX-loaded HA-CCMs were shown to effectively suppress the progression of MDA-MB-231 tumor and significantly extend mice survival time. These hyaluronic acid-shelled and disulfide-crosslinked micelles with great simplicity and selectivity are highly promising for treating various CD44-overexpressing cancers.